Perlindungan Hukum Terhadap Justice Collabolator Dalam Perkara Pidana Korupsi - Tiara Yuda Istiqa (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractCorruption is an extraordinary and difficult problem to eradicate so that one of the responsibilities in the Corruption Criminal Court is needed to resolve other corruption cases. The witness of the offender or known as the Justice Collaborator is a secret leaker who works with Law Enforcement Officials to dismantle another crime by giving information or testimony to the crime he has committed with his colleagues. A person who is a witness or a criminal is very much getting threats from outside parties, both for himself and for his family. Therefore, legal protection is needed that guarantees the safety of the witnesses given. Legal protection is the protection given to every citizen is no exception, because Indonesia is a legal state that upholds the values of justice and law enforcement and human rights. Protection of Justice Collaborator has been regulated in Law Number 31 of 2014 as regards Protection of Witnesses and/or Victims. In the Law, a Justice Collaborator has the right to get protection for his personal, family and property security, and is free from Threats relating to the testimony that he will, is or has given. Witness Actors have the right to obtain protection, this is in accordance with the LPSK and the 1945 Constitution regulations, so that the state is obliged to respect, protect and fulfill human rights, even though the Justice Collaborator is someone who has committed a crime.Keywords: Legal Protection, Justice Collaborator, Corruption.